Implementing point‐of‐care ultrasonography of the heart and lungs in an anesthesia department. Issue 2 (February 2017) - Bøtker, M. T.; Vang, M. L.; Grøfte, T.; Kirkegaard, H.; Frederiksen, C. A.; Sloth, E.
Abstract : Background: Implementation of point‐of‐care ultrasonography (POCUS) of the heart and lungs requires image acquisition skills among providers. We aimed to determine the effect of POCUS implementation using a systematic education program on image acquisition skills and subsequent use and barriers in a department of anesthesiology. Methods: Twenty‐five anesthesiologists underwent a systematic education program in POCUS during the fall of 2012. A POCUS expert evaluated images from baseline and evaluation examinations performed on two healthy individuals as useful or not useful for clinical interpretation. In August 2016, anesthesiologists employed at the department answered a questionnaire regarding the use of POCUS and perceived barriers to its use. Results: The systematic education program increased the proportion of images useful for clinical interpretation from 0.70 (95% CI 0.65–0.75) to 0.98 (95% CI 0.95–0.99). This difference was significant when adjusted for prior cardiac ultrasonography courses, prior clinical cardiac ultrasonography experience, ultrasonography view, and ultrasound model ( P < 0.001). After 3.5 years, 15/25 (60%) of perioperative medicine providers, 22/24 (92%) of intensive care providers, and 21/21 (100%) of pre‐hospital care providers used POCUS either routinely, in selected patient groups, or sporadically. Conclusion: Implementation of POCUS by a systematic education program increased image acquisition skills across anesthesiologists employed at the department. POCUS was used in the intensive care setting, the pre‐hospital setting, and to a lesser extent in the perioperative setting. Educational strategies for obtaining images under difficult conditions, practical equipment and evidence for effect on patient outcomes are required for full implementation of POCUS.